Cluster analysis of post-COVID-19 physical and mental health outcomes 3–6 months after SARS-CoV-2 infection: results of the French Prospective ALCOVID Cohort Study - Philippe Halfon; Laurent Chiche; Hervé Pegliasco; Stanislas Rebaudet; Thomas Escoda; Hervé Faralli; Frédéric Cohen (BMJ Open)
Objectives This study aims to characterise the diversity of post-COVID-19 physical and mental health outcomes, known as the post-COVID-19 condition (PCC), and the determining factors 3–6 months after acute SARS-CoV-2 infection.Design This is a prospective cohort study.Setting This study took place at the European Hospital of Marseille, France.Participants Participants include patients with acute COVID-19 treated as inpatients or outpatients.Interventions Interventions include face-to-face assessment of physical and mental health symptoms.Main outcome measures Main outcome measures include symptom scores and scales, as well as paraclinical elements (thoracic CT scan, pulmonary functional tests). Multiple component analysis was used to identify clinical phenotypic clusters of PCC patients, as well as their initial comorbidity groups. A multinomial regression model was used to evaluate the association between the initial comorbidities and disease severity with PCC phenotype.Results A total of 210 patients agreed to participate, of which 157 (75%) reported at least one symptom at the 3–6 months visit; mostly asthenia, dyspnoea, psychiatric disorders such as anxiety, depression, post-traumatic stress disorder and cognitive disorders. Four PCC clusters were recognised: (1) paucisymptomatic PCC (n=82, 39%); (2) physical sequelae PCC (n=39, 18.6%), (3) pre-existing pulmonary comorbidities PCC (n=29, 13.8%); and (4) functional somatic and/or mental symptoms PCC (n=60, 28.6%). In addition to their PCC symptoms, the patients in these clusters differed in terms of their demographic characteristics (sex), comorbidities and severity of COVID-19.Conclusions The four identified PCC clusters corresponded to distinct and coherent clinical and paraclinical entities, making it possible to consider adapted and personalised prognosis and therapeutic interventions.